Penerapan Extreme Programming dalam Pengembangan Sistem Informasi Manajemen Pelayanan Publik - Nurkholis, Andi; Susanto, Erliyan Redy; Wijaya, Suhenda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Sukarame District serves public administration activities such as information on population data and mail administration services. The conventional process currently running in Sukarame District only uses Microsoft Office for data storage so that it cannot be accessed by people in real-time. As a solution to the problem, we need a system that can help public service management to manage population data, public complaints, and service letters such as environmental permits, electricity subsidy permits, and business permits. This system was developed with the extreme programming development method with system design using a unified modeling language, namely use case diagram, class diagram, and activity diagram. To assess the feasibility of the system, testing was carried out using the black-box method which resulted in an accuracy of 100%, so that this system was fit for use functionally.